Property Enhancement During Artificial Aging of Al6061- Silicon Oxide Metal Matrix Composites. (2018) - Prakash, Y.M. Shiva; Shankar, M.C. Gowri; Karthik,; Sharma, S.S.; Kini, Achutha
Abstract: In the current work Al6061- Silicon oxide (SiO2 ) composites are produced by two stage stir casting method and subsequently studied various properties. Microstructure, hardness, tensile and wear properties of Al6061 based composite having 2, 4 and 6% wt.% of SiO2 is analyzed and presented. The aging behavior and tensile properties of the cast material were studied. Experimental results show homogeneous dispersal of the SiO2 particles in the matrix leading to substantial improvement in the mechanical properties. Presence of SiO2 particulate in aluminium matrix alloy hastening the aging kinetics and thus attains improvement in strength. These particulates offer short circuit path for nucleation of fine precipitates to hinder the movement of dislocation and thus increases hardness as well strength of materials. After aging at 100°C for Al6061/6% wt. SiO2 composite, highest strength is observed at longer duration of aging. Comparison of the characteristics study before and after heat treatment was done and it is revealed that there is an enhancement in hardness, ultimate tensile strength and wear resistance of both Al6061 alloy and its composites after precipitation hardening treatment